Children's Perceptions of Obesity and Health: A Focus Group Study With Hispanic Boys - Skelton, Joseph A. (2012)
OBJECTIVE: Hispanic boys are one of the most at-risk groups for the development of obesity, yet few effective interventions have been reported. The objective of this study was to assess Hispanic boys' perceptions of health and obesity to inform future, targeted interventions. METHODS: This is a qualitative and quantitative study of Hispanic boys aged 8 to 12 years in Forsyth County, North Carolina (n = 25). Three focus groups were conducted combined with anthropometrics and measures of body image. Interview guides were developed to elicit children's perceptions of obesity, nutrition, physical activity, and family influences over health behaviors. Focus group comments were recorded and transcribed. Transcripts were coded using a multistage inductive approach, and grounded theory was used to analyze responses. RESULTS: The following 6 themes emerged: boys had a limited and superficial understanding of health, nutrition, and activity; perceptions of health were based on muscular appearance, frequency of exercise, and media messages; boys had negative perceptions of overweight children and physical performance; family meals were infrequent and unstructured; boys prefer restaurants with fast food, buffets, and entertainment; and neighborhood safety influences activity participation. Boys did not mention parents as influencers of health and habits. CONCLUSIONS: From their findings, the authors have outlined several key areas that will inform clinicians and researchers in the prevention and treatment of obesity in this highly vulnerable population.